PENEGAKAN HUKUM PELANGGARAN MODIFIKASI TANDA NOMOR KENDARAAN BERMOTOR BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN OLEH KEPOLISIAN SATUAN LALU LINTAS RESOR KOTA PEKANBARU - IKA FELASTRI; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Traffic violation is a disregard for the rules of traffic carried by the vehicles that cause traffic accidents for other road users, both loss of life and injuries. Number sign violation modification of motor vehicles is a problem that is quite complex, due to the modification of the number sign motor vehicle is mostly done by societies that generally have a vehicle.The purpose of the study is to examine the enforcement of the law against modification Signs Number of Motor Vehicles, to determine the obstacles encountered in the enforcement of the law against modification Signs Number of motor vehicles and to know the efforts to overcome the constraints of law enforcement for the modification Signs Number of Motor Vehicles based under the Act number 22 Year 2009 Regarding Traffic and Road Transportation.From the research results can be concluded that problem. Law enforcement against modification Signs Number of Motor Vehicles implemented by the City Police Pekanbaru through two (2) attempts, by making efforts preventive and repressive efforts. Constraints faced is the shortage for the manufacture of Motor Vehicle Numbers Signs. Then intervention by unscrupulous people and law enforcement officers. Furthermore, the efforts made to overcome these obstacles is the way, providing temporary Motor Vehicle Numbers Signs, and do outreach to the community and law enforcement officials. Suggestions authors, law enforcement is expected to mark number of Vehicle modifications to be maximized given the cultured use Signs modification Number of Motor Vehicles and more attention to the provision of sign making materials Number of Motor Vehicles.Keywords: Law Enforcement-violation-Signs Number of Motor Vehicles